No change in the consumption of thyroid hormones after starting low dose naltrexone (LDN): a quasi-experimental before-after study - Guttorm Raknes; Lars Småbrekke (BMC Endocrine Disorders, 2020)
Abstract Background Low dose naltrexone (LDN) is reported to have beneficial effects in several autoimmune diseases. The purpose of this study was to examine whether starting LDN was followed by changes in the dispensing of thyroid hormones to patients with hypothyroidism. Methods We performed a quasi-experimental before-after study based on the Norwegian Prescription Database. Study participants were identified by using reimbursement codes for hypothyroidism. Cumulative dispensed Defined Daily Doses and the number of users of triiodothyronine (T3) and levothyroxine (LT4) 1 year before and after the first LDN prescription was compared in three groups based on LDN exposure. Results We identified 898 patients that met the inclusion criteria. There was no association between starting LDN and the subsequent dispensing of thyroid hormones. If anything, there was a tendency towards increasing LT4 consumption with increasing LDN exposure. Conclusion The results of this study do not support claims of efficacy of LDN in hypothyroidism.